Neonatal Exposure to Estradiol Valerate Increases Dopamine Content in Nigrostriatal Pathway During Adulthood in the Rat - Jara-Picas, P (Georg Thieme Verlag, 2014)
Research in programming has focused in the study of stimuli that affect sensitive periods of development such as prenatal and neonatal stage. We previously showed that exposure to estradiol valerate to female rats during the first 12h of life increased catecholamine content in ventromedial-arcuatus hypothalamus of the adult rat. However, changes in others dopaminergic circuits have not been studied. The purpose of this work was to determine the neurotransmitters changes induced by neonatal estradiol valerate (0.1mg/50?l s. c. per rat) administration on nigrostriatal pathway of adult female rats. Sesame oil (50?l s. c. per rat) was administered in a control parallel group. EV-1 adult rats presented effective markers of long-term estrogenization as decreased serum levels of progesterone and a reduction in the size of estrogen-sensitive organs. In the brain, neonatal estradiol valerate administration led to a significant increase in dopamine content in striatum, substantia nigra and ventral tegmental area. With respect to the contents of dopamine metabolites, only 3-methoxytyramine content increased in substantia nigra and ventral tegmental area. In addition, the content of noradrenaline increased only in striatum. Interestingly, estrogenized rats lacked locomotor activity induced by acute dose of amphetamine (1mg/kg i. p.). Altogether, these results show that neonatal exposure to estradiol valerate permanently modified the content of monoamine neurotransmitters in nigrostriatal pathway and amphetamine-induced locomotor activity of adult female rats. This might imply that estrogenized rats could have changes in the expression of key proteins in dopaminergic regulation, as tyrosine hydroxylase and dopamine transporter.© Georg Thieme Verlag KG Stuttgart. New York.